Evaluation of Primary School Teachers’ Competence in Implementing 2013 Curriculum: A Study in Tomohon City - Moreen Zedko Isaura Sumual; Mohammad Ali (Journal of Education and Learning (EduLearn), 2017)
Teachers play an important role in curriculum implementation and become one of the factors in it. The role of teachers in the implementation of curriculum is influenced by the competence they have. This study aimed to examine the correlation between pedagogical competence and teacher’s teaching experience in Tomohon city primary schools. The study used descriptive method with correlational study model. The data used in this study was secondary data based on the results of UKG 2015. The selected research subjects were elementary school teachers in Tomohon especially in schools that had implemented 2013 Curriculum. The data analysis method used in this study was Pearson Product-Moment Correlation. The results of this study indicates that teaching experience and pedagogical competence are negatively correlated (r = -0.403), and the correlation is significantly indicated by p-value of 0.000. This means the longer the teaching experience, the less pedagogical competence are the teachers.